Effectiveness of Implementing APITO (Online Residency Permit Registration Application) for Foreign Nationals at the Class I Special Immigration Office of TPI Ngurah Rai - Marcopo, Jonathan; Mustofa, Amirul; Widyawati, Widyawati (PT. Anagata Sembagi Education, 2024)
This research aims to analyze the effectiveness of implementing APITO (Online Stay Permit Registration Application) for foreign nationals at the Ngurah Rai Special Class I Immigration Office. APITO was introduced as a digital solution to simplify the stay permit registration process for foreign nationals entering Indonesia. This research focuses on five main indicators for evaluating APITO's effectiveness: program comprehension, target accuracy, timeliness, goal achievement, and tangible impact on users and related institutions. The research method employed in this study is a qualitative approach, where data was collected through in-depth interviews, observation, and document analysis related to APITO’s implementation. The findings indicate that, in general, APITO’s application is quite effective, with varying effectiveness percentages across each indicator. The program comprehension indicator shows an effectiveness rate of 72%, but more efficient communication is still needed to enhance users’ understanding of application procedures. The target accuracy indicator shows an effectiveness of 68%, with challenges in providing clearer guidance for new users. Meanwhile, in terms of timeliness, the application achieves 74% effectiveness, indicating a positive accomplishment though system reliability can still be improved. The conclusion from this study indicates that APITO has the potential to enhance the quality of immigration services for foreign nationals, although several aspects require refinement. Based on these findings, it is recommended that the Immigration Office strengthen technical infrastructure such as internet networks and server capacity, especially during peak periods of stay permit requests. Additionally, brief training or socialization on APITO usage should be provided for foreign users, both offline at airports and online via video guides. Multi-language support is also recommended to help users from various countries access the application more easily.